Clinico-radiological profile of CVT patients and its correlation with D-dimer. (August 2020) - Pathak, Abhishek; Nath Chaurasia, Rameshwar; Kumar Singh, Varun; Shukla, Upasana; Joshi, Deepika; Nath Mishra, Vijaya
Highlights: Cerebral venous thrombosis (CVT) has equal predilection among both sexes. Most common symptom is headache. Puerperal period is a major risk factor for CVT in females even in present era. CVT patients should be evaluated for the presence of iron deficiency anemia. Positive D-dimer assay should raise the suspicion of CVT in patients with acute headache. Abstract: Cerebral Venous Thrombosis (CVT) is a well-known disease with diverse clinical presentation and causes. With advances in neuroimaging and changing lifestyles, the clinical profile and causes of CVT are changing. D-dimer has been studied in early diagnosis of CVT with variable results. This prospective study was carried out to assess the clinical profile of CVT and role of D-dimer in early diagnosis of CVT. The study period was from September 2017 to July 2019 and included 32 imaging proven patients of CVT. We also included 32 patients of migraine for assessing D-dimer. Data was collected according to a preformed format. D-dimer was assessed by a rapid semi-quantitative latex agglutination assay. Out of 32 CVT patients, 16(50%) were females. The mean age of the patients was 31.56 ± 14.31 years. Most common clinical features were headache (96.25%), papilloedema (37.5%) and seizures 10 (31.25%). Puerperium was the most common cause of CVT in females. Superior sagittal and transverse sinuses were the most common sinuses to be affected. The sensitivity of D-dimer assay was 81.25% and specificity 62.5%. Cerebral venous thrombosis is a disease with equal predilection among both genders affecting mostly young individuals. Most of the patients present with headache. Puerperium still contributes to majority of the cases. Iron deficiency anaemia needs to be evaluated as an association for CVT. Positive D-dimer should strengthen the suspicion of CVT in patients with acute headache.